2019
DOI: 10.1177/1028315319842342
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Study Abroad Student Inflows and Outflows: An Institutionalist Perspective

Abstract: The determinants of study abroad student inflows and outflows are analyzed by comparing the faculties of all Czech public universities. The article develops an institutionalist theoretical perspective that views higher education institutions not only as passive senders and receivers of students but also as active gatekeepers that regulate student flows by balancing the inflows with outflows and vice versa. The theoretical argument is developed against the backdrop of existing theories that emphasize the “push–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
3
0
3
Order By: Relevance
“…A study by Garrett et al (2017) found that student mobility is an important element in the strategies of most IBCs, but actual student participation is often not as high as aimed for. Whereas institutions are often able to balance study abroad inflows and outflows between institutions (Kouba, 2020), they appear less able to balance inflows and outflows between home campuses and IBCs. Many IBCs successfully act as feeder institutions, sending students to the home campus, but few, if any, receive as many incoming students from the home campus.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Garrett et al (2017) found that student mobility is an important element in the strategies of most IBCs, but actual student participation is often not as high as aimed for. Whereas institutions are often able to balance study abroad inflows and outflows between institutions (Kouba, 2020), they appear less able to balance inflows and outflows between home campuses and IBCs. Many IBCs successfully act as feeder institutions, sending students to the home campus, but few, if any, receive as many incoming students from the home campus.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, demand for local tertiary students was estimated by Levatino (2017), and Cattaneo et al (2019), based on the physical distance between the local cities and the local universities. From a contradicting perspective, distance is less important when considering other factors as determined by Mazzarol and Soutar (2002), Li and Bray (2007), Bodycott (2009), Migin et al (2015), and Kouba (2019). The distance factor may also influence in other ways, which are caused by regional and remoteness effects, as explained in the study by S'a et al (2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Estudantes matriculados; estudantes internacionais, que moram na Austrália, matriculados; estudantes internacionais, que não moram na Austrália, matriculados; distância, idioma comum (dummy), PIB do país de origem, população, taxa de estudantes no ensino superior, taxa de estudantes internacional no ensino superior, taxa de desempregados, visto é necessário (dummy), EI_matriculados (variável independente). Kouba (2020) Analisar os determinantes da entrada e saída de estudantes de e para o exterior, comparando-se as faculdades de todas as universidades públicas tchecas.…”
Section: O Uso De Modelos Gravitacionais Para Levantar Os Determinant...unclassified
“…Outro aspecto a ser considerado é que o recrutamento de mais alunos pode envolver a comunicação de recursos que não estão conectados com a universidade em si, mas sim aspectos como a localização, o tamanho da cidade e os benefícios associados ao estudo transnacional, como aponta Kouba (2020). Nos estudos listados, os determinantes relacionados aos custos de trânsito e acadêmico (BEINE; NOËL; RAGOT, 2014; BESSEY, 2012), a qualidade de vida (EFENDI et al, 2020;KAZEMI et al, 2018;KOUBA, 2020), a política pública destinada aos estudantes internacionais (BARNETT et al, 2016;KOUBA, 2020;LEVATINO, 2017), a dimensão e reputação do sistema nacional de ensino superior (ALTBACH, 2012;BARNETT et al, 2016;BEINE;NOËL;RAGOT, 2014), as fortes relações culturais ou políticas entre os países de origem e o destino (BEINE; NOËL; RAGOT, 2014; SÁ; SABZALIEVA, 2016; SIN; ANTONOWICZ; WIERS-JENSSEN, 2019) e o idioma inglês como idioma de instrução (ALTBACH, 2012; WANG, 2020) para estudantes internacionais são apontados como importantes determinantes para atração de estudantes internacionais.…”
Section: O Uso De Modelos Gravitacionais Para Levantar Os Determinant...unclassified
See 1 more Smart Citation